Sigillo sacramentale e segreto ministeriale. La tutela tra diritto canonico e diritto secolare (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Sigillum confessionis, secretum, intimitas, segreto, riservatezza, privacy - 2. Nuove questioni alla luce di recenti sviluppi sullo scenario nazionale e mondiale - 3. La disciplina del ‘segreto ministeriale’ in Italia nella normativa unilaterale e in quella bilaterale - 4. Gli interessi tutelati, tra ordinamento canonico e ordinamento italiano - 5. Un problematico arresto della Corte di Cassazione - 6. La lotta alla ‘piaga della pedofilia’ - 7. Le risposte del diritto canonico universale, in particolare l’obbligo di denuncia - 8. Le Linee guida della Conferenza Episcopale Italiana - 9. Incidenze sul tema trattato. La Nota della Penitenzieria Apostolica sull’importanza del foro interno e l’inviolabilità del sigillo sacramentale del 29 giugno 2019 - 10. Le ragioni e le strategie della protezione del segreto ministeriale. La giusta tutela della libertà religiosa.The safeguard of the sacramental seal and the priest-penitent privilege between Canon law and Secular lawABSTRACT: The essay analyzes the interferences between - on one hand - recent developments in Canonical Penal law and in some State laws in order to strengthen the prevention and the repression of child sexual abuse committed by clerics and religious, and - on the other hand - the safeguard of the secrecy of the sacred ministers with regard to the informations that the faithful confide to them precisely because of their quality. In fact, there are currently tendencies in legislation and jurisprudence which tend to compress - if not to deny - the safeguard of the secrecy of such relations, risking to call into question the protection of an extremely important aspect of freedom of conscience and of religion, which is an outcome of a protracted historical evolution that has been safeguarded - at least in Italy - satisfactorily and effectively until now. The aim of the paper is to clarify the reasons underlying the involved juridical institutions, both in Canon law and in State law, in order to suggest solutions which - by preserving and promoting them - conform to justice.
Keywords: Ministri di culto